The comparison of crossword puzzles and chemopoly learning media on Students’ cognitive learning results In the hydrocarbon concept - Riana Antika Amahoroe (12 Waiheru, 2022)
The implementation of the cooperative learning model of the team games tournament (TGT) type using learning games media is one solution to overcome the problems of tedious learning chemistry. The study aimed to determine whether there are differences in student learning outcomes of hydrocarbons in the first Experimental class (I) by using Crossword Puzzle media and the second Experimental class (II) by using Chemopoly media. This study used an experimental method with a pre-experimental design. The sample was taken using techniques of cluster random sampling retrieved from 2 classes. First Experimental class (I), XI-4 using cooperative learning model in the type of TGT which is equipped with crossword puzzles and Experiments Class II, XI-5 using cooperative learning model in the type of TGT which is equipped by Chemopoly. Data collected was used to test techniques and analysis of the data using an unpaired t-test. The results showed that Crossword Puzzle media gained higher learning outcomes than Chemopoly media usage. In Experiment, I class there were 10 students (38.46%) with very good qualifications and 16 students (61.54%) with good qualifications. Meanwhile, in the Experiment II class, there were 5 students (19.23%) with very good qualifications, 18 students (69.23%) with good qualifications, and 3 students (11.54%) with moderate qualifications.